2000
DOI: 10.1139/g00-059
|View full text |Cite
|
Sign up to set email alerts
|

Molecular contribution to selection of intergeneric hybrids between sugarcane and the wild species Erianthus arundinaceus

Abstract: Erianthus arundinaceus has great potential as a germplasm source for better ratoonability, vigour, tolerance to environmental stresses, and disease resistance in sugarcane. Many unsuccessful attempts have been made to introduce these characters into modern sugarcane cultivars. We report on significant progress made since molecular tools were implemented. Sequence-tagged PCR, revealing size variation in the 5S rDNA cluster, was performed on intact leaf tissue to identify genuine hybrids six weeks after germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 13 publications
4
80
1
2
Order By: Relevance
“…Similar caution should be taken with morphological characters when they are used as diagnostic markers. In the past, morphology has often been misleading in the interpretation of the results of artificial inter-genera crosses, especially those involving Saccharum and Erianthus (D'Hont et al 1995; Piperidis et al, 2000).…”
Section: The Evolutionary Path Leading To Sugarcanementioning
confidence: 99%
“…Similar caution should be taken with morphological characters when they are used as diagnostic markers. In the past, morphology has often been misleading in the interpretation of the results of artificial inter-genera crosses, especially those involving Saccharum and Erianthus (D'Hont et al 1995; Piperidis et al, 2000).…”
Section: The Evolutionary Path Leading To Sugarcanementioning
confidence: 99%
“…In the S. officinarumϫE. arundinaceus hybrids studied by fluorescent in situ hybridization by Piperidis et al (2000) 6 hybrids had fewer than 70 chromosomes expected from nϩn transmission and 1 hybrid had approximately 78 chromosomes, 50 of which were contributed by S. officinarum and 28 by E. arundinaceus, was attributed to 2nϩn transmission. Chromosome elimination occurred in all the hybrids studied by them.…”
Section: Discussionmentioning
confidence: 95%
“…Erianthus arundinaceus is a large grass with tall and thick stalks resembling sugarcane and having useful traits such as growth vigour, wide ecological adaptability, extensive root system, drought and water logging resistance, good ratoonability, high biomass and disease resistance (D'Hont et al 1995). E. arundinaceus is being used in the sugarcane breeding programmes for introgression of favourable agronomic characters from E. arundinaceus to sugarcane but the non-flowering or sterility of many of the hybrids with S. officinarum was a limiting factor (Piperidis et al 2000). The wide crosses of sugarcane with the wild species S. spontaneum and E. arundinaceus are being done to improve the biomass yield of sugarcane as an energy crop (Ming et al 2006).…”
mentioning
confidence: 99%
“…Most of these species have relatively large chromosomes. Nevertheless, GISH analyses of Nicotiana and sugarcane cultivars have shown that the small chromosomes of these species originate from different ancestral genomes, which can clearly be discriminated (Lim et al, 2000;Piperidis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%